SYNTHESIS OF OLIGOPEPTIDES OF DEFINED FRAGMENT COMPOSITION - Tamara Paypanova; Tatyana Hristova; Rumyana Cherkezova (Peytchinski Publishing, 2011)
The advantages of the solid-phase peptide synthesis were used. The peptide chain was built on specially processed insoluble polymer resin: Wang- and Rink Amide MBHA-resin. Three new fragment oligopeptides were prepared by activation and condensation of Fmoc-protected amino acids [which were subject of our previous work]. One of the important advantages of Fmoc-strategy is achieved: no continuous unblocking of the protection group is effected and the formed peptide bonds do not break.